2022
DOI: 10.1038/s41598-022-14544-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adhesive coating on calcium, phosphate, and fluoride release from experimental and commercial remineralizing dental restorative materials

Abstract: This study investigated the potential of adhesive coating for hindering the reactivity of ion-releasing dental restorative materials. Experimental composites were prepared by replacing 10 or 20 wt% of reinforcing fillers with two types of bioactive glass. A glass ionomer, a giomer, and an alkasite were used as representatives of commercial ion-releasing materials. Restorative material specimens were coated with an etch-and-rinse adhesive, 1-step self-etch adhesive, 2-step self-etch adhesive, or left uncoated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Similar considerations were also expressed in the study by Wang et al [ 29 ] in which they investigated the effects of the coating on initial fluoride release from resin-modified glass-ionomer cements [ 29 ]. Another study by Par et al [ 30 ] came to similar conclusions by demonstrating that fluoride release from coated specimens of the alkasite composite (Cention) was reduced 300-fold compared to the uncoated specimens [ 30 ]. In contrast to these results, Tay et al [ 31 ] suggested that adhesives may act as permeable membranes that allow remineralization of tooth structure and arrest the caries process.…”
Section: Discussionmentioning
confidence: 77%
“…Similar considerations were also expressed in the study by Wang et al [ 29 ] in which they investigated the effects of the coating on initial fluoride release from resin-modified glass-ionomer cements [ 29 ]. Another study by Par et al [ 30 ] came to similar conclusions by demonstrating that fluoride release from coated specimens of the alkasite composite (Cention) was reduced 300-fold compared to the uncoated specimens [ 30 ]. In contrast to these results, Tay et al [ 31 ] suggested that adhesives may act as permeable membranes that allow remineralization of tooth structure and arrest the caries process.…”
Section: Discussionmentioning
confidence: 77%
“…When the same resin system was functionalized with 10 wt% of three different BG compositions, even higher water sorption was measured (107.4–132.7 μg/cm 3 ). Such a highly hydrophilic resin system was not required for experimental composites in our study because the hydrophilicity of the unsilanized BG particles themselves allowed sufficient water diffusion, as demonstrated in previous in vitro studies of the same experimental composites regarding ion release [ 21 , 42 ] and protective effects on dental hard tissues [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the experimental composites that tended to form a thick resin-rich layer (F-10 and F-40), these procedures would also improve calcium phosphate precipitation by exposing BG particles. In any case, the different thicknesses of the resin-rich layer observed in the experimental composites deserve further investigation, as this layer may influence the caries-preventive effect by isolating reactive fillers from the aqueous environment and reducing their dissolution, as well as the release of remineralizing ions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in this systematic review investigated Ca, P and F release using atomic absorption spectrometry (for Ca), ultraviolet-visible (UV-Vis) spectroscopy (for P), and ion-selective electrode analysis (for F) 47,48) . Par et al reported that the resinous adhesive layer could act as a barrier for ion release, significantly reducing the remineralization properties of restorative materials.…”
Section: Qualitative Study and Outcome Measuresmentioning
confidence: 99%